Imaging Characteristics of Perosomus elumbis in a Puppy - Sooyoung Choi; Byungho Lee; Byungdon Lee; Jiwon Seo; Hyunyoung Park; Kyunghun Kwon; Youngwon Lee; Hojung Choi (The Korean Society of Animal Reproduction and Biotechnology, 2015)
A 4-day-old, male Poodle dog was presented with dull, depressed and exhausted activity after the birth. On physical examination, the puppy showed arthrogryposis, muscular atrophy and no movement of hindlimbs. Palpation on dorsum revealed an absence of lumbar and sacral vertebrae. On prenatal and postnatal radiography, lumbar vertebrae, sacrum and coccygeal vertebrae were not visualized. On ultrasonography, bilateral kidney and urinary bladder were observed. On computed tomography, there were no apparent abnormalities in the forelimbs, cervical vertebrae or head, while lumbar vertebrae, sacrum and coccygeal vertebrae were not observed. At necropsy examination, the liver, stomach, intestine, kidney and urinary bladder were normal. This congenital anomaly was consistent with Perosomus elumbis. Perosomus elumbis in dogs is a rare condition of unknown etiology. In this report, Perosomus elumbis was evaluated with radiography, ultrasound and computed tomography.